2007
DOI: 10.1537/ase.051202
|View full text |Cite
|
Sign up to set email alerts
|

Non-metric dental trait variation among local sites and regional groups of the Neolithic Jomon period, Japan

Abstract: Inter-populational heterogeneity of the Neolithic Jomon hunter-gatherers of Japan was examined via 21 non-metric dental traits. Skeletal samples from nine local sites and five regional groups of the middle to final stages of the Jomon period were analyzed, and inter-site comparisons were made among five representative sites (Ubayama, Nakazuma, Ikawazu, Yoshiko, and Tsukumo). Statistically significant differences were found in 4/21 traits in the inter-site comparisons, and in 5/21 traits in the inter-regional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…These findings suggest that the Jomon had an overall flatter face in Okinawa than in Honshu, which also accords with previous observations (Wakebe et al, 1996;Nagashima and Wakebe, 2003). Nevertheless, this minor distinction would not refute the previous view that the extent of geographical diversity of the Jomon craniofacial form was modest relative to intra-group variations of other East Asian groups including the modern Japanese (Dodo, 1982;Yamaguchi, 1982;Kondo, 1994;Matsumura et al, 2001;Matsumura, 2007;Hanihara and Ishida, 2009;Ishida et al, 2009). Suda (1940) undertook an anthropometric survey on the faces of live inhabitants of Okinawa Prefecture, and asserted that a low/broad facial proportion and a low nasal height are noteworthy features of this population.…”
Section: Discussionmentioning
confidence: 89%
“…These findings suggest that the Jomon had an overall flatter face in Okinawa than in Honshu, which also accords with previous observations (Wakebe et al, 1996;Nagashima and Wakebe, 2003). Nevertheless, this minor distinction would not refute the previous view that the extent of geographical diversity of the Jomon craniofacial form was modest relative to intra-group variations of other East Asian groups including the modern Japanese (Dodo, 1982;Yamaguchi, 1982;Kondo, 1994;Matsumura et al, 2001;Matsumura, 2007;Hanihara and Ishida, 2009;Ishida et al, 2009). Suda (1940) undertook an anthropometric survey on the faces of live inhabitants of Okinawa Prefecture, and asserted that a low/broad facial proportion and a low nasal height are noteworthy features of this population.…”
Section: Discussionmentioning
confidence: 89%
“…Within the Japanese archipelago, contrasting opinions on the population structure of the Jomon have been proposed: the Jomon people were relatively homogeneous (Dodo, 1982;Yamaguchi, 1982;Kondo, 1994;Ossenberg et al, 2006;Matsumura, 2007) or heterogeneous (Adachi et al, 2009a, b;Hanihara and Ishida, 2009;Nakashima et al, 2010). When comparing the ancient populations of the Japanese archipelago (Kanto, Tohoku, and Hokkaido Jomons and Okhotsk), the population differentiation test demonstrated that they were statistically different from each other (highest P-value was 0.007 between the Tohoku and Hokkaido Jomon).…”
Section: Population Comparison Based On Haplogroup Frequenciesmentioning
confidence: 99%
“…The Jomon are widely thought to have settled the Japanese archipelago c. 15700 to 2350 years BP (Kobayashi, 2008) and ranged geographically from Hokkaido to Okinawa. Morphological studies of dental variation have suggested that the Jomon people were of southern origin (Turner, 1987(Turner, , 1990Hanihara, 1991;Matsumura, 2007;Matsumura et al, 2009). On the other hand, archaeology, genetics, and recent cranial morphology studies suggest that the Jomon people were of northern origin (Nei, 1995;Imamura, 1996;Omoto and Saitou, 1997;Hanihara and Ishida, 2009;Nakashima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, analysis of 21 dental non-metric traits revealed that the regional differences are quite limited, with the five regional Jomon subsamples of Hokkaido, Tohoku, Kanto, Tokai, and Sanyo showing a tight cluster (Matsumura, 2007).…”
Section: Regional Variation In Jomon Skeletal Remainsmentioning
confidence: 78%
“…Previous analyses on cranial and dental morphologies suggested that the ancestral population of the Jomon people originated from Southeast Asia (Turner, 1987;Hanihara, 1991;Matsumura, 2007), whereas other morphological analyses (Hanihara and Ishida, 2009;Nakashima et al, 2010) and mtDNA sequence data (Adachi et al, 2009) suggested that their ancestors were of Northeast Asian origin. A new nuclear genomic sequence of a Sanganji Jomon (Tohoku region) specimen indicated that the Jomon people were derived from an ancestral East Eurasian population prior to the currently recognizable population diversification (Kanzawa-Kiriyama et al, 2016), as previously mentioned from an osteological point of view (Yamaguchi, 1992).…”
Section: Discussionmentioning
confidence: 97%